Sorghum genotype screening for increased productivity on marginal land through the ratoon cropping system. Issue 1 (April 2020) - Faesal,; Syuryawati,; Suarni,
Abstract: Sorghum as a drought tolerant crop, its planting is directed to marginal dry land type agro-climate which is relatively hotter for the supply of alternative food for rice substitution. The food sorghum genotype was selected from a multilocation test of 15 accessions plus Numbu variety, local Lombok and local Flores, so that there were 18 accessions arranged according to the randomized block design with three replications as the main crop. Spacing of 75 cm x 20 cm (66, 666 plants per ha), fertilized with 135 kg N, 45 kg P2O5 and 60 kg K2O per ha on the main crop. After the main crop has been harvested, relatively homogeneous shoots are kept as ratoon plants until harvest and are fertilized 1 time as much as 50% of the main crop fertilizing dose after the shoots begin to grow. The results showed that five sorghum genotypes in the ratoon cultivation system produced higher seeds than superior varieties of Numbu and were significantly higher than those of Flores and local Lombok. Sorghum genotypes that provide high profits from two seed harvests (main crop yields > 6 t / ha and sorghum rations > 5 t / ha) compared to three comparative varieties, especially Numbu, are genotypes No. 58-1 (Rp. 14, 922, 700); 86-1 (Rp. 13, 954, 200); 11-5 (Rp. 13, 936, 000); 113-1 (Rp. 13, 905, 000); and No. 103-1 (Rp. 13, 006, 800) while Numbu benefits Rp. 12, 178, 500 / ha. This is supported by higher genotype farming efficiency values, ranging from R/C of 2.36 - 2.53 and B/C of 1.36 - 1.53 and lower cost per kg ratio of Rp 790 - 846 / kg of temporary seeds Numbu value of R/C 2.26; B/C 1.26 and the cost/kg ratio of seeds is Rp 884.